Evaluation of pedicle screw placement by pedicle channel grade in adolescent idiopathic scoliosis: should we challenge narrow pedicles? - Akazawa, Tsutomu; Kotani, Toshiaki; Sakuma, Tsuyoshi; Minami, Shohei; Tsukamoto, Satoshi; Ishige, Miho (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2015)
Surgeons often have concerns about whether to place screws in narrow pedicles for correction of scoliosis. The aim of this study was to use pedicle channel grades based on preoperative CT to evaluate pedicle screw placement in posterior surgery for adolescent idiopathic scoliosis. The subjects comprised 55 patients who underwent posterior correction and fusion, and a total of 810 pedicles were examined in which screw placement had been planned and probing had been performed. Pedicle channel grades were determined by measuring inner pedicle diameter on preoperative CT scans. The grades were defined as grade 1 with an inner diameter of>4mm, grade 2 with an inner diameter of>2mm and<4mm, grade 3 with an inner diameter of>1mm and<2mm, and grade 4 for a “cortical channel” with an inner diameter of<1mm. Results The failure rate of screw placement was 0.5 % for pedicle channel grade 1, 2.9 % for grade 2, 12.0 % for grade 3, and 31.5 % for grade 4, showing significant differences (p<0.001). For the laterality of curvature, the failure rate was 5.9 % for the convex side, 8.0 % for the neutral vertebra, and 9.0 % for the concave side, showing no significant difference. There was also no significant difference in failure rate between degrees of curvature of<60° (8.2 %) and>60° (5.6 %). Logistic analysis showed that the pedicle channel grade was a significant risk factor for failure (odds ratio 4.0, p<0.001). The failure rate of screw placement was 31.5 % for a cortical channel with a pedicle inner diameter of<1mm. Screw placement should be attempted in pedicles with an inner diameter of 1mm or larger.